Looking Back to Move Forward: Lessons From Three Decades of Research and Management of Cetacean Tourism in New Zealand - Fumagalli M; Guerra M; Brough T; Carome W; Constantine R; Higham J; Rayment W; Slooten E; Stockin K; Dawson S (Frontiers Media S.A., 2021)
Cetacean tourism in Aotearoa New Zealand is now over 30 years old and has experienced substantial growth in visitor numbers and operations. The industry is remarkably diverse, targeting several dolphin and whale species, and encompassing varied habitats in coastal waters, fiords and submarine canyons. The knowledge and experience collected over these past 30 years has both advanced the global understanding of cetacean tourism, and influenced scientific practices for its study and management. Here we review the approaches taken in quantifying the impact of cetacean tourism in New Zealand, and critically assess the efficacy of the research and management strategies adopted. We place particular focus on the Bay of Islands, Hauraki Gulf, Kaikoura, Akaroa and Fiordland, areas that include the oldest, and longest studied industries nationally. We propose a set of best research practices, expose the most notable knowledge gaps and identify emerging research questions. Drawing on perspectives from the natural and social sciences, we outline the key determinants of failure and success in protecting cetacean populations from the detrimental impact of tourism. We suggest four golden rules for future management efforts: (1) acknowledge cetacean tourism as a sub-lethal anthropogenic stressor to be managed with precaution, (2) apply integrated and adaptive site- and species-specific approaches, (3) fully conceptualize tourism within its broader social and ecological contexts, and (4) establish authentic collaborations and engagement with the local community. Lastly, we forecast upcoming challenges and opportunities for research and management of this industry in the context of global climate change. Despite New Zealand's early establishment of precautionary legislation and advanced tourism research and management approaches, we detected flaws in current schemes, and emphasize the need for more adaptive and comprehensive strategies. Cetacean tourism remains an ongoing challenge in New Zealand and globally.
Keywords: whale watching; dolphin swim-with; wildlife tourism; tourism impact; cetacean conservation; impact research; tourism management